IS ISLAMIC BANKING RIBA FREE ? (CASE STUDY : MURABAHA CONTRACT) - Adi Martono (EAJ (Economic and Accounting Journal), 2018)
Islamic banks is established to provide solutions on the need for transactions and financing facilities to the Moslem who want to avoid riba and gharar. From the previous researches, author obtains facts and conditions : 1) Moslem people think Islamic banks still implement contract and transaction contain riba or they do not comply with Holy Qur’an and Sunnah of Prophet. 2) In executing murabaha contract, Islamic banks under study have not possessed or controled the goods before they sells it to the customer. To find out how and why those facts and conditions happen in Islamic bank, author uses case study as research methodology. After after analyzing the implementation of murabaha contract from previous researches and comparing it to the sharia standards, authorfound there are gaps between the murabaha contract that has been implemented in several Islamic bank and in sharia standard. In this case, author uses sharia standard issued by Accounting and Auditing Organization for Islamic Financial Institution (AAOIFI). Those gaps are implementation of wakalah contract, possession of goods and implementation of murabaha contract. Islamic bank should improve the process or mechanism of those contract. The conclusion is because lack of understanding about that Islamic banks have to improve the process of Murabaha contract, such as the process of acquisition of goods so the process refers to the Holy Qur’an and the Sunnah of Prophet.